The Analysis of Pulsed Electromagnetic Field Effect on Solution Conductivity - Novan Agung Mahardiono; Hanif Fakhrurroja; V. Luvita; Sudaryati Cahyaningsih (Research Center for Chemistry - LIPI, 2016)
This paper presents the observation of magnetization process variableswhich influenced the conductivity of FeSO4, MnSO4, MgCl2 and CaCl2solution. Some of the survey results revealed that there was a decrease inthe rate of particle formation of FeSO4, MnSO4, MgCl2 and CaCl2 of theions in the sample of the magnetized hard water. This study compared theconductivity of FeSO4, MnSO4, MgCl2 and CaCl2 solution before and afterthe pulsed electromagnetic field with a concentration level of 0.1 M wasgiven. Electromagnetic Water Treatment (EW) was used to generate theelectromagnetic pulse wit 9.3 mT pulsed electromagnetic filed. Tools Themeasurement of solution conductivity level conducted using BenchConductivity Meter was calibrated by Control Company with certificatenumber 4163-4997748 and traceable to the National Institute of Standardsand Technology. The measurement was conducted by observing the timefunction of solution conductivity of FeSO4, MnSO4, MgCl2, and CaCl2.The results showed that pulsed electromagnetic fields affected theconductivity of FeSO4 and CaCl2 solution by74% and 67%, respectively.Meanwhile, the lower conductivity was observed from MnSO4 and MgCl2solution with 6% due to process of magnetization which caused theinstability of the ionic bonding in the solution.